1996
DOI: 10.1038/380720a0
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil rolling altered by inhibition of L-selectin shedding in vitro

Abstract: The L-selectin adhesion molecule is involved in guiding leukocytes to sites of inflammation. L-selectin is cleaved by an unusual proteolytic activity at a membrane-proximal site resulting in rapid shedding from the cell surface. Although it has been demonstrated that L-selectin mediates, in part, the early event of leukocyte rolling under hydrodynamic flow, the contribution of shedding to L-selectin function has remained unknown. Here we show that hydroxamic acid-based metalloprotease inhibitors block L-select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
201
2
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 263 publications
(213 citation statements)
references
References 32 publications
9
201
2
1
Order By: Relevance
“…Hydroxamic acid-based metalloprotease inhibitors have been shown by us and others to inhibit activation-induced L-selectin proteolysis [13,[18][19][20]. We observed that the hydroxamic acid-based metalloprotease inhibitor KD-IX-73-4 also completely blocked rottlerin and calphostin C-induced L-selectin shedding ( Fig.…”
Section: Selective Pkc Inhibitors Induce L-selectin Down-regulationsupporting
confidence: 59%
See 2 more Smart Citations
“…Hydroxamic acid-based metalloprotease inhibitors have been shown by us and others to inhibit activation-induced L-selectin proteolysis [13,[18][19][20]. We observed that the hydroxamic acid-based metalloprotease inhibitor KD-IX-73-4 also completely blocked rottlerin and calphostin C-induced L-selectin shedding ( Fig.…”
Section: Selective Pkc Inhibitors Induce L-selectin Down-regulationsupporting
confidence: 59%
“…Staurosporine, wortmannin, H89, KT5823, genistein, and K252b were purchased from Alexia (San Diego, CA); Gö-7874, Ro-31-8220, bisindolylmaleimide 1, rottlerin, and calphostin C were purchased from Calbiochem (San Diego, CA). KD-IX-73-4, a hydroxamic acid-based metalloprotease inhibitor, has previously been shown to block activation-induced L-selectin shedding [13,18]. All kinase inhibitors and KD-IX-73-4 were dissolved in dimethyl sulfoxide (DMSO) and diluted at least 1000-fold for all whole-cell assays.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…E-mail: mullbergj@immunex.com Abbreviations: TNFR-Fc, soluble form of the p80 TNFR linked to the constant region of the human Ig heavy chain cells [12] and shedding of the p60 TNFR and IL-6R from transfected cells and human primary monocytes [13]. A recent study demonstrated that TAPI blocks the release of L-selectin and TGFcc from transfected cells [14] and hydroxamates have also been shown to inhibit L-selectin shedding from primary cells [15][16][17]. Other proteins whose release is blocked by TAPI or related compounds include the thyrotropin receptor [18], Fas ligand [19], heparin-binding EGF-like growth factor [20] and angiotensin-converting enzyme [21].…”
Section: Introductionmentioning
confidence: 99%
“…1A) was initially examined using an in vitro shear flow assay that allows for cellular analyses under hydrodynamic conditions simulating the microvasculature (29,30,32). CHO-131 ϩ and CHO-131 Ϫ CLA ϩ CD3 ϩ T cells were first isolated from the peripheral blood of normal individuals by sorting, and then the shear resistance of each subset was assessed over Nonspecific Ab labeling was determined using the appropriate isotype negative control Abs, as indicated.…”
Section: P-selectin Binding Activity By Cho-131mentioning
confidence: 99%